Comparative effects of isometric and isotonic global neck muscles strengthening exercise program on pain, range of motion, strength, function and quality of life in patients with chronic mechanical neck pain - Amjad, Misha; Shakil Ur Rehman, Syed; Fatima, Ghulam; Ikram, Mehwish; Ghafoor, Sobia (Journal of the Pakistan Medical Association, 2024)
The randomised clinical current study was planned to determine the comparative effects of isometric and isotonic global neck muscles strengthening exercises on pain, range of motion, strength, function and quality of life in patients with chronic mechanical neck pain. The study comprised 22 patients with chronic mechanical neck pain. The subjects were randomly divided into two interventional groups, with group A receiving isometric exercises and group B receiving isotonic exercises. Numeric Pain Rating Scale, Neck Disability Index, goniometer, dynamometer and Short Form-36 questionnaire were used for data collection. Isometric and isotonic exercise groups showed significant improvement (p<0.05) in terms of decreasing pain and functional disability, and increasing range of motion and strength. Intergroup comparison showed no significant differences (p>0.05), indicating similar efficacy of isometric and isotonic global neck muscles strengthening exercises. Trial Registration Number: This study was registered at ClinicalTrials.gov ID: NCT05865951.